Ordre de la Resemblance: ett bidrag till Nordenflychtforskningen - Önnerfors, Andreas (1700-tal: Nordic Journal for Eighteenth-Century Studies, 2011)
This article treats an episode in the life and work of one of the most prominent Swedish female poets of the eighteenth century, Hedvig Charlotta Nordenflycht (1718-1763). Based upon a letter to one of her friends, earlier research has speculated on whether Nordenflycht established a fraternal order. New archival evidence suggests that this indeed seems likely. In the collections of the Swedish Order of Freemasons a manuscript has resurfaced after a 150-year hibernation, outlining ‘Grund och Reglor til Ordre de la Resemblance’ (Foundations and rules for the order of resemblance). This document, dated 15 October 1747, is introduced by a poem, ‘Förstånds och Hjertas ädlaste syssla’ (The most noble activity of reason and the heart), treating the moral perfectibility of man, the search for the light of truth, and hailing friendship as a secret force of attraction, an invisible magnetic power causing ‘resemblance’ between humans. Developed out of these motifs, twelve subsequent paragraphs elaborate the ideology and organization of the order, resembling other forms of organized sociability of the time. Whoever drew up these rules and regulations must have been familiar with similar forms of fraternal orders during the period as well as the idea of female participation. A shared codex of moral behavior, a motto, an emblem, and organizational principles for membership and association were codified. In 1753 Nordenflycht joined an outspokenly literary order, the Order of the Edification of Thought (Tankebyggarorden), and it appears likely that either the experience or the mere concept of the ‘Ordre de la Resemblance’ facilitated Nordenflycht’s membership. This concept, if it was realized, might have advanced the creation of a horizontal network-style community intended to participate in male spheres of dominance. The ‘Ordre’ can be interpreted as an extended textual praxis in which a text was performed in social interplay beyond its textual qualities. Interpreted from the perspective of theories of performance, the ‘Ordre’ reflects a development towards the renegotiation, redefinition, and reform of manners during the time catalyzed by organized associational life and ritual performance.